Quarters, Five Layers of Happiness: Can urbanship make people happier? - Lidin, Konstantin (project baikal, 2015)
In everyday life quarters are often perceived as urban fragments divided according to peculiarities of the lifestyle (urbanship). Every variation of urbanship has a corresponding conception of happiness. Thus, only urbanistic decisions on a quarter scale can make citizens happier. City, regional and country scales are too big, and the variety of forms of urbanship (and corresponding visions of happiness) is too wide there to search for uniform ways of optimization of the city environment.